Corporate governance and tax avoidance in emerging markets: does political connection matter? - Bani Alkausar; Prinintha Nanda Soemarsono; Annisa Wulandari; Nitami Galih Pangesti; Ajeng Rachma Pertiwi; Azrul Abdullah (Journal of Multiperspectives on Accounting Literature, 2026)
Purpose – This study examines the role of a Corporate Governance on corporate tax avoidance and whether political connection moderates this relationship in Indonesian listed firms. Methodology/approach - This study employs panel data regression with pooled Ordinary Least Squares (OLS) based on Common Effect Model (CEM). It is based on a sample of 323 firms listed on the Indonesia Stock Exchange in 2015–2022, yielding 2,584 firm-year observations. Findings – The findings show that stronger corporate governance is associated with lower corporate tax avoidance. However, its influence is more evident in firms' tax payment behaviour than in tax deferral practices. Political connection does not alter the role of corporate governance in shaping corporate tax avoidance. Practical implications - This study imply regulators could strengthen governance supervision and tax compliance, whereas companies should improve their governance quality to lessen opportunistic taxation conduct and reputation loss. Novelty – This study provides new evidence on the role of political connection in the governance and tax avoidance relationship within the institutional context of Indonesia.